Pernikahan Siri Dan Implikasinya Terhadap Hak Dan Identitas Anak - Herlina Herlina; Muhammad Rifa’I; Fhirley Fhirley; Dwi Noviani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Siri marriage is still a social phenomenon, which is quite widespread and has become an area of ​​debate in society. The practice of unregistered marriages is carried out by people who do not understand the law, although it does not rule out the possibility that unregistered marriages are carried out by people who understand the law. For some people who still think that unregistered marriage is the best way out and there is no element of sin in it because it has been done, according to religion, it's just not registered through a marriage registrar by the religious affairs office so it doesn't have clear evidence. Even if it is understood in terms of consequences law, then unregistered marriages have an impact on problems that will occur not only for the wife but also for the status of the children. Even though a siri marriage is a marriage that meets the requirements for harmony of marriage, for certain reasons, it is not registered at the religious affairs office. The basic things felt by women carrying out betel marriages include; psychological problems and mental stress as a result of legal uncertainty regarding his marital status. This psychological burden also occurs because of society's stereotypes of women in unregistered marriages who are considered mistresses, pregnant out of wedlock, cheaters and so on, and will affect their education and the most important thing is their religious education. This research uses library research. The method used in this research is a normative juridical research method. Normative juridical research is legal research carried out by examining library or secondary materials. In the library research method, the author uses secondary data, namely data obtained from library materials, such as; books, journals, and more.